Analytical Decision Supports System for Urban Air Quality Management in Tehran: Meteorological and Photochemical models - Hossein Shahbazi; Vahid Hosseini; Yousef Rashidi; Parya Broomandi (Iranian Journal of Health, Safety and Environment, 2018)
A new analytical air pollution modeling system is introduced in this paper to estimate concentrations of primary and secondary air pollutants and using it for further studies in order to improve the knowledge of pollutants emission and dispersion over Tehran, and developing a decision support system. For this purpose, WRF/CAMx modeling system was used to simulate the gas-phase pollutants concentrations including primary and secondary pollutants, over Tehran during a wintertime episode, which is characterized by very high concentrations of pollutants. Pollutants were triggered by meteorological conditions leading to a forced holiday imposed on citywide operations to protect the health of citizens. Based on calculated Values of NMB error, WRF performs acceptable in predicting temperature and wind speed. Generally, time series plots show that WRF performs acceptable in mild selected episode. Also, the daily trends of pollutant concentrations are greatly affected by changes in local meteorological conditions such as planetary boundary layer (PBL) height, temperature, wind, and relative humidity over the Tehran area. An underestimation in prediction of all pollutants concentrations episode at Poonak and Aghdasyeh sites show due to the insufficient emission data at the site position used for the simulation were seen. Results showed that WRF/CAMx modeling system proved to be a useful tool for analyzing urban environmental problems, investigating the impact of air quality control policies, and predicting critical conditions. However, there were weaknesses in input data and modeling system calibration that should be improved before using the system for further studies.